2003
DOI: 10.1046/j.1095-8649.2003.00128.x
|View full text |Cite
|
Sign up to set email alerts
|

Post mortem shrinkage of four species of temperate and tropical marine fishes, without freezing or preservation

Abstract: The present study indicated significant post mortem decreases in length for four Australian teleost species from temperate to tropical habitats: black bream Acanthopagrus butcheri, King George whiting Sillaginodes punctata, summer whiting Sillago ciliata and redthroat emperor Lethrinus miniatus. Shrinkage averaged 5·0 mm after 24 h (range 0–10 mm) for A. butcheri, 4 mm (0–8 mm) for S. punctata, 2·2 mm (0·7–3·7 mm) for S. ciliata and 5·4 mm (−2·5–15·0 mm) for L. miniatus. For A. butcheri held under three differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
25
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(31 citation statements)
references
References 18 publications
6
25
0
Order By: Relevance
“…The proportion of seahorses Z10 cm at capture that would be expected to shrink below the MSL due to desiccation (as in Morison et al, 2003) was calculated using the size frequency of seahorse bycatch reported for three seahorse species, H. guttulatus (Curtis and Vincent, 2006), H. hippocampus (Curtis, 2004; J Curtis, unpublished data) and H. erectus (Baum et al, 2003). Catch data for H. guttulatus (n 5 2733) and H. hippocampus (n 5 281) were obtained from thawed seahorses captured during an unrelated study (Erzini et al, 2002) and height was measured as a straight line (Curtis, 2004;Curtis and Vincent, 2006).…”
Section: Potential Implications For Msl Enforcementmentioning
confidence: 99%
See 4 more Smart Citations
“…The proportion of seahorses Z10 cm at capture that would be expected to shrink below the MSL due to desiccation (as in Morison et al, 2003) was calculated using the size frequency of seahorse bycatch reported for three seahorse species, H. guttulatus (Curtis and Vincent, 2006), H. hippocampus (Curtis, 2004; J Curtis, unpublished data) and H. erectus (Baum et al, 2003). Catch data for H. guttulatus (n 5 2733) and H. hippocampus (n 5 281) were obtained from thawed seahorses captured during an unrelated study (Erzini et al, 2002) and height was measured as a straight line (Curtis, 2004;Curtis and Vincent, 2006).…”
Section: Potential Implications For Msl Enforcementmentioning
confidence: 99%
“…Despite a rich body of literature that documents the shrinking effects of mortality and preservation on the body lengths of fishes (Hay, 1982;Fowler and Smith, 1983;Leslie and Moore, 1986;Kruse and Dalley, 1990;DiStefano et al, 1994;Fisher et al, 1998;Morison et al, 2003), few studies have investigated the implications of shrinkage for the enforcement of size limits (Mapstone et al, 2004). Minimum size limits (MSLs) are widely applied as tools for regulating recreational and commercial fisheries (Perry et al, 2002;Morison et al, 2003;Mapstone et al, 2004).…”
Section: Introductionmentioning
confidence: 98%
See 3 more Smart Citations